Hubungan Pola Makan dan Kualitas Penggunaan Sunscreen SPF ≥ 30 dengan Kejadian Acne Vulgaris pada Mahasiswa Generasi Z: Penelitian - Prakoeswa, Flora Ramona Sigit; Fatimah, Lina Nur; Dzikri, Dykall Naf'an; Sutrisna, Em; Fithriyah, Sa’idatul (Cermin Dunia Kedokteran, 2026)
Introduction: Acne vulgaris (AV) is an inflammatory disorder of the pilosebaceous follicles that commonly affects adolescents and young adults. AV is influenced by multiple factors, including diet and the use of cosmetic products such as sunscreen. This study aimed to analyze the association of dietary patterns and the quality of SPF ≥ 30 sunscreen use with AV among Generation Z university students. Methods: This analytical observational study used a cross-sectional design and included 108 eligible respondents. Data were collected using questionnaires on dietary patterns and quality of sunscreen use, as well as a clinical examination for AV. Bivariate analysis was performed using Fisher’s exact test. Results: Dietary patterns among Generation Z were not significantly associated with the presence of acne vulgaris (p = 0.609). The quality of SPF ≥ 30 sunscreen use was also not significantly associated with the incidence of acne vulgaris (p = 0.441). Conclusion: Neither dietary patterns nor the quality of SPF ≥ 30 sunscreen use showed a statistically significant association with the incidence of acne vulgaris in the study sample. Further studies with larger populations and multivariable analyses are needed to evaluate other potential confounding factors.